Pengaturan Tindak Pidana Zina Dalam KUHP Dikaji Dari Perspektif Living Law - Sahran Hadziq (Lex Renaissance, 2019)
The regulation of adultery in the Indonesian legal system has several elements that are incompatible with the meaning of adultery in living law in the society. Article 284 of the Indonesian Criminal Code (KUHP) prohibits sexual intercourse by a couple outside the wedlock or the forbidden sexual relations. However, one element in this Article stipulates that sexual relations are only prohibited and may be subjected to the Article only if one of the offenders is married. Therefore, according to these elements, it is natural for the public to interpret that infidelity cannot be considered as adultery. Using a socio-legal and historical approach, this study aims to examine the regulation of criminal acts of adultery both in the Criminal Code and from the perspective of the law that lives in the society, which has a discrepancy between one another. The results show that there are many discrepancies or ineffectiveness between the applicable regulation and the reality in the society. These discrepancies are also found in the elements of such applicable law, which results in the inability to apply the adultery article in the community. Therefore, there must be an effective and efficient form of adultery regulations in Indonesia that are in line with the law that lives in the society.